ANALISIS TINGKAT KOMPONEN DALAM NEGERI (TKDN) PADA PROYEK RENOVASI RUMAH DINAS KANTOR PELAYAN PAJAK DI KABUPATEN SIKKA - kaidu, Triapriono; Soludale, Anastasia M.N. (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The primary objective of this study is to analyze the domestic content components in the renovation project of the KPP Pratama Maumere official residence. Domestic content is a strategic government policy based on several perspectives. Specifically, this policy is implemented to encourage demand for local products and labor while strengthening the local economic base. This research employs a descriptive quantitative approach to evaluate quantitative data related to materials, labor, and services used in the project. The findings reveal that the final domestic content value percentage (TKDN) for the renovation project of the KPP Pratama Maumere official residence, influenced by the use of local materials, reaches 70.40%. This indicates that the project has exceeded the minimum TKDN threshold of 35%. Thus, no evaluation or financial penalties are required, as these are only applicable if the project fails to meet the established minimum TKDN threshold. The study highlights that material components have the most significant influence on the final TKDN value of this project